Effect of ectoparasite infestation density and life‑history stages on the swimming performance of Atlantic salmon Salmo salar - S Bui; T Dempster; M Remen; F Oppedal (Aquaculture Environment Interactions, 2016)
To overcome sustainability obstacles and improve operations, the Atlantic salmon farming industry is testing novel approaches to production. Redistributing farm sites to offshore locations is one such solution; however, tolerance to high-current velocity sites must be considered, particularly if fish health status is compromised by parasites. We tested the effect of parasite density and life-history stage on the swimming performance of Atlantic salmon Salmo salar using a swim flume. Salmon with 3 different salmon lice Lepeophtheirus salmonis densities (0, 0.02 ± 0.01 and 0.11 ± 0.01 lice cm-2 [mean ± SE]) were tested across the 4 major life-history stages of lice (copepodid, chalimus, pre-adult and adult) for critical swimming performance (Ucrit). Salmon Ucrit declined slightly by a mean of 0.04 to 0.10 body lengths s-1 with high parasite densities compared to uninfested and low densities, across the lice stages, while progression through the parasite life-history stages had little effect on swimming performance. Our results suggest that increasing infestation density of salmon lice incurs negative fitness consequences for farmed Atlantic salmon held in high-current velocity sites, with little difference in costs associated with attachment by different life-history stages of the lice.